Zero-derivation in Korean: the effect of covert structure in real-time processing - Kim, Nayoun; Li, Ziying; Byeon, Seonghyeon; Lee, Chaejin (Frontiers in Psychology, 2023)
Korean words like balgda ‘bright/become bright’ and gilda ‘long/become long’ are categorially ambiguous; they can appear as both adjectives and verbs. Some suggest that these words are listed under separate lexical entries, while others propose that they share one single lexical entry, and that the verb form is morphologically derived from the base adjective through a process called zero derivation. This study presents the results of a real-time experiment that investigates whether these words involve zero derivation and if so, how zero derivation may affect the real-time processing of these words. Our findings suggest that the reader recognizes the base adjective and obtains the derived-verb form by virtue of adding a covert category-changing morpheme in real-time sentence processing. This study provides promising evidence of the zero derivation of Korean categorially ambiguous adjectives and verbs, as well as crosslinguistic evidence of the role of covert structure in lexical access.